Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Ask your questions and receive precise answers from experienced professionals across different disciplines. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the value of [tex]\( x \)[/tex] in the equation [tex]\( 2x + 3y = 36 \)[/tex] when [tex]\( y = 6 \)[/tex], follow these steps:
1. Substitute [tex]\( y = 6 \)[/tex] into the equation:
[tex]\[ 2x + 3(6) = 36 \][/tex]
2. Simplify the equation by calculating [tex]\( 3 \cdot 6 \)[/tex]:
[tex]\[ 2x + 18 = 36 \][/tex]
3. Next, isolate [tex]\( x \)[/tex] by subtracting 18 from both sides of the equation:
[tex]\[ 2x + 18 - 18 = 36 - 18 \][/tex]
Simplify:
[tex]\[ 2x = 18 \][/tex]
4. Finally, solve for [tex]\( x \)[/tex] by dividing both sides by 2:
[tex]\[ x = \frac{18}{2} \][/tex]
Simplify:
[tex]\[ x = 9 \][/tex]
Thus, the value of [tex]\( x \)[/tex] is [tex]\( \boxed{9} \)[/tex].
1. Substitute [tex]\( y = 6 \)[/tex] into the equation:
[tex]\[ 2x + 3(6) = 36 \][/tex]
2. Simplify the equation by calculating [tex]\( 3 \cdot 6 \)[/tex]:
[tex]\[ 2x + 18 = 36 \][/tex]
3. Next, isolate [tex]\( x \)[/tex] by subtracting 18 from both sides of the equation:
[tex]\[ 2x + 18 - 18 = 36 - 18 \][/tex]
Simplify:
[tex]\[ 2x = 18 \][/tex]
4. Finally, solve for [tex]\( x \)[/tex] by dividing both sides by 2:
[tex]\[ x = \frac{18}{2} \][/tex]
Simplify:
[tex]\[ x = 9 \][/tex]
Thus, the value of [tex]\( x \)[/tex] is [tex]\( \boxed{9} \)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.